The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1080/00029157.1993.10403036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preventive Measures in Reducing Aftereffects to Hypnosis

Abstract: In the present study we assessed the efficacy of several procedures in minimizing the occurrence of aftereffects of a hypnotic induction. We gave experimental subjects (n = 347) a brief lecture dispelling some myths about hypnosis, told them no psychological treatment would be undertaken, and then administered the Harvard Group Scale of Hypnotic Susceptibility, Form A (HGSHS:A) in which all references to aftereffects had been removed. We gave the standard version of the HGSHS:A to control subjects (n = 340). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Some evidence also suggests prehypnosis expectations predict aftereffects on the HGSHS:A (Coe, Peterson, & Gwynn, 1995). Hypnotizability, therefore, has been shown to predict somatic complaints following a hypnosis session, with high hypnotizability being associated with more aftereffects (Page & Handley, 1993. It is unknown whether hypnotizability is also associated with greater somatic complaints in day-to-day life.…”
Section: Jarred W Younger Et Almentioning
confidence: 96%
See 1 more Smart Citation
“…Some evidence also suggests prehypnosis expectations predict aftereffects on the HGSHS:A (Coe, Peterson, & Gwynn, 1995). Hypnotizability, therefore, has been shown to predict somatic complaints following a hypnosis session, with high hypnotizability being associated with more aftereffects (Page & Handley, 1993. It is unknown whether hypnotizability is also associated with greater somatic complaints in day-to-day life.…”
Section: Jarred W Younger Et Almentioning
confidence: 96%
“…Early reports on somatic aftereffects of standardized research hypnosis protocols showed the most common symptoms to be headache, drowsiness, nausea, and HYPNOTIZABILITY, SOMATIC COMPLAINTS, AND GENDER 3 dizziness (Orne, 1965). Roughly 3% of research participants may experience adverse effects, although scales using more cognitive (Stanford Hypnotic Susceptibility Scale, Form C; SHSS:C; Weitzenhoffer & Hilgard, 1962) than ideomotor (Harvard Group Scale of Hypnotic Susceptibility, Form A; HGSHS:A; Shor & Orne, 1962) items may cause a much higher incidence of somatic aftereffects (Crawford, Hilgard, & Macdonald, 1982;Page & Handley, 1993). Some evidence also suggests prehypnosis expectations predict aftereffects on the HGSHS:A (Coe, Peterson, & Gwynn, 1995).…”
Section: Jarred W Younger Et Almentioning
confidence: 99%
“…The association between hypnosis with an unpleasant childhood event has been a potent source of negative reactions involving revivification of emotionally laden and somatic events (or taking the form of retrograde amnesia), and alterations of arousal with autonomic signs. Sequelae have included chronic depression and PTSD symptoms (Gruzelier, 2000b(Gruzelier, , 2004; dissociative episodes following age regression to the time of WWII trauma (Kleinhauz, Dreyfuss, Behan, Goldberg and Azikri, 1979); surgical operations in childhood involving the alteration and reduction of consciousness with anaesthetic (Hilgard et al, 1961); the production of stupor (Kleinhauz and Behan, 1981); and the reinstatement of epilepsy (Page and Handley, 1993). Where there were multiple memory cues in this associative network of negative episodes, adverse effects may be compounded (Page and Handley, 1993).…”
Section: Thalamo-cortical Functionsmentioning
confidence: 97%
“…By a selective shutting down of customary everyday frontal executive and inhibitory functions, hypnosis provides access to past memories of cognitive, affective and somatic events (Damasio's 'somatic marker'). This may explain how somatic memory, including surgical operations in childhood that involve the alteration and reduction of consciousness with anaesthetic (Hilgard, Hilgard and Newman, 1961), and the reinstatement of epilepsy (Page and Handley, 1993), may arise with hypnosis.…”
Section: Thalamo-cortical Functionsmentioning
confidence: 99%
See 1 more Smart Citation